Design, fabrication and testing of an electrochemically based DNA biosensor for detection of Coniella Granati fungal disease of pomegranate fruit and aster yellows bacterial grapevine disease - Madufor, Kennedy John Ndubuisi (Stellenbosch : Stellenbosch University, 2019)
Thesis (MEng)--Stellenbosch University, 2019.